POTENSI BEBERAPA LARUTAN ORGANIK DALAM MENDUKUNG PRODUKSI BAWANG MERAH (Allium ascalonicum) - Milawati Lalla; Suwandi Said (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2021)
Red unions are one type of plant that is widely used as a  spice ini cooking and cannot be replaced with other types of plants so it is needed every time.   The research objective was to obtain one type of organic solution that produced the highest production of shallots and to calculate the potential production of each given organic  solution.  The research was carried out at the Kebun Percontohan Balai Penyuluhan Pertanian Bulango Timur in January-April 2020.  The research was conducted in the form of Randomized Bloc design consisting of 8 treatments including control namely without the use of organic solutions, POC, MOL Rice, MOL Banana, ZPT red union, ZPT Tauge, PGPR Root Bamboo and PGPR Elephan Grass Root.  Repeat 3 times with a plot size 1 m x 1 m.  The parameters observed were fresh weight and dry weight of red union bulbs.  The results showed that the highest fresh weight was obtained from the treatment of ZPT red union  14,22 ton haˉ¹) and MOL banana (14,06 ton haˉ¹).  The highest dry weight of bulbs resulted from the MOL treatment of banana (9,93 ton haˉ¹) and ZPT red union (9,87 ton haˉ¹).